Antinociceptive Activity of Methanol Extract of Tamarix indica (Bangladesh Journal of Physiology and Pharmacology, 2010)
The antinociceptive activity of the methanolic extract of the barks of Tamarix indica Roxb. was investigated using acetic acid-induced writhing model in swiss albino mice. The extract produced about 26.89%( P< 0.01) and 43.55% (P< 0.001) writhing inhibition at the dose of 250 and 500 mg/ kg of body weight respectively, which was comparable to the standard drug diclofenac sodium where the inhibition was about 63.64% (P< 0.001) at the dose of 25 mg/kg of body weight. At the above doses, the extract exhibited significant and dose dependent antinociceptive activity in acetic acid-induced writhing model in swiss albino mice. Phytochemical investigation of the extract indicate the presence of reducing sugars, tannins, gums, flavonoids and saponin. Key words: Tamarix indica; antinociceptive activity; acetic acid-induced writhing; phytochemical test. DOI: 10.3329/bjpp.v25i1.5736Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 1-3